Comparing online and traditional interview techniques : a qualitative study of the experiences of researchers and participants in the Malaysian context - Diyana, Kamarudin (2015)
As technology mediated communication is being incorporated into everyday life, more and more people log on to the internet every dày. There is no longer a distinction between the online world and the offline world, where the activities in these worlds have become increasingly merged in our society; the two spaces interact and therefore transform each other (Garcia, Standlee, Bechkoff & Yan Cui, 2009). In the online environment, direct interaction are replaced with computer screen data that could include combinations of visual, aural, kinetic and textual components. Society has become so used to it that they do not see it as being a combination of the components, but rather as an extension of them (Garcia et al., 2009). Even though the online and offline world has increasingly merged, there is not a lot of research done on the internet as a tool to conduct interviews over long distance. Learning how to maximize and fully utilize the internet for academics or research purposes such as data collection method, as well as understanding their strengths and weaknesses seems to be a constant new frontier to delve into (Curasi, 2000).